2011
DOI: 10.1016/j.ccr.2011.04.010
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic Rationale for Inhibition of Poly(ADP-Ribose) Polymerase in ETS Gene Fusion-Positive Prostate Cancer

Abstract: Summary Recurrent fusions of ETS genes are considered driving mutations in a diverse array of cancers, including Ewing’s sarcoma, acute myeloid leukemia, and prostate cancer. We investigate the mechanisms by which ETS fusions mediate their effects, and find that the product of the predominant ETS gene fusion, TMPRSS2:ERG, interacts in a DNA-independent manner with the enzyme poly(ADP-ribose) polymerase 1 (PARP1) and the catalytic subunit of DNA protein kinase (DNA-PKcs). ETS gene-mediated transcription and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
315
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(332 citation statements)
references
References 53 publications
14
315
0
3
Order By: Relevance
“…In a recent report two independent cohorts of over 100 patients were treated with external beam radiotherapy (Dal Pra et al 2013). Although preclinical studies predicted that TMPRSS2-ERG tumors might be more sensitive to radiation (Brenner et al 2011), the presence of the gene fusion showed no association with biochemical recurrence-free survival in the clinical study. So, a simple extrapolation of experimental data to the clinical setting seems not to be possible and other factors not included in the clinical analyses so far contribute to clinical behavior.…”
Section: Ets Fusions As Diagnostic and Prognostic Markers Of Prostatementioning
confidence: 99%
“…In a recent report two independent cohorts of over 100 patients were treated with external beam radiotherapy (Dal Pra et al 2013). Although preclinical studies predicted that TMPRSS2-ERG tumors might be more sensitive to radiation (Brenner et al 2011), the presence of the gene fusion showed no association with biochemical recurrence-free survival in the clinical study. So, a simple extrapolation of experimental data to the clinical setting seems not to be possible and other factors not included in the clinical analyses so far contribute to clinical behavior.…”
Section: Ets Fusions As Diagnostic and Prognostic Markers Of Prostatementioning
confidence: 99%
“…The ERG transcription factor encoded by TMPRSS2-ERG fusion is known to drive cell invasion and metastases, induce DNA damage in vitro, and focal pre-cancerous prostatic intraepithelial neoplasia (PIN) lesions in transgenic mice (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…If an oncogenic mechanism is discovered, previous work has reported that ERG interacts in a DNA-independent manner with the enzyme poly (ADP-ribose) polymerase 1 (PARP1). This provides a basis for the use of PARP1 inhibitors, and studies have shown inhibition of xenograft PA growth in ETS-positive, but not ETS-negative tumors [23]. While significant hurdles remain before clinical utility, the potential exists for the first directed therapy against SCC.…”
Section: Discussionmentioning
confidence: 99%